Students’ Self-Regulation in Learning Academic Writing with AI Mediation Tools - Abdul Hadi; Kusworo Aribowo; Dodi Erwin Prasetyo (Journal of English Language and Education, 2026)
Academic writing is developed by rehearsal. It requires further practice. Therefore, this paper aimed at finding to explore  the integration of self-regulated learning for university students in academic writing with AI mediation learning tools and to explore those strengths. This paper applied library research. Thus, the data were gained from scientific journal, proceeding, research articles, books, and so forth where those should be relevant with the topic discussed. The finding underscored two points. The first was that how integrate Artificial Intelligence AI with self-regulated learning a writing skills. The second, the benefits regarded on those integration. The recommendation was delivered in the pedagogic and future research aspects. For pedagogic, educators curriculum maker and AI experts should discuss together to set valuable curriculum, learning writing materials, instructions and so forth.  For future researcher, further researches should be conducted with the different study level, and different language skills to analyze comprehensively toward those integrations in order to gain wider perspectives.